Developing a new paradigm for performance of educating city theory in advanced technology mega-cities, case: Tehran, Iran - Amini, Masoome; Mahdavinejad, Mohammadjavad; Bemanian, Mohammad Reza; Varzaneh, Elham Hatami (Journal of Architecture and Urbanism, 2014)
Considering the growth of the world’s population and the need for educated individuals, the development of technology among the young generation, is now felt more than ever. This issue offers countless opportunities for education. So, many urban managers and city authorities try to consider all available options to achieve this goal. Nowadays, educating cities are the framework for development on local, civil and commercial levels all over the world. Tehran as the capital of Iran is a city where people with different cultures and expectations live. This means that the city authorities must perform various programs to satisfy people’s expectations, thus the role of urban management is extremely valuable, and MPOs must make intelligent decisions in this area. The goal of this paper is to examine the current state of Tehran and the projects related to its potential as an educating city in recent years, and also to evaluate the capability of Tehran to advance to the state of the educating city. The key question is: “How does Tehran fulfill the prerequisites of the principles for educating cities?” And “Which criteria need to be reconsidered for this purpose?” The results of the research show that Tehran has a lots of obstacles had yet to be overcome to meet Educating City goals and objectives.